Chiral to Chiral Phase Transition in a Novel Hydrogen Bond Type Molecular Ferroelectric. Issue 28 (26th July 2018) - Yang, Changshan; Tan, Yuhui; Wang, Changfeng; Chen, Shaopeng; Wen, Herui; Tang, Yunzhi
Abstract: Although great progress has been made for H‐bonds type molecular ferroelectrics, the systems accompanying with chiral to chiral phase transitions are still very spare. Here we display a new hydrogen bond type molecular ferroelectric, the salt of 1‐(1‐naphthyl) ethylammonium‐nopinate, 1, which undergoes a paraelectric–ferroelectric phase transition around 202 K from one chiral point group ( P 21 21 21 ) to another chiral point group ( P 21 ). The electric hysteresis loop under 100 K directly indicates it is a potential ferroelectric material with maximum spontaneous polarization ( P s ) 2.3 uC /cm 2 . X‐ray single crystal diffraction analysis shows that the significant hydrogen bond change along the b ‐axis direction results net dipole moment and leads to the spontaneous polarization. The exceptional dielectric response in the vicinity of 202 K exhibits remarkable dielectric anomalies along the b ‐axis direction than the other two directions. The strong SHG (second harmonic generation) signal (‐1.31) without obvious changes dependence on temperature further confirm the chiral to chiral structural phase transition. Abstract : The H‐bonds type molecular ferroelectric1 undergoes a paraelectric–ferroelectric phase transition around 202 K from one chiral point group ( P 21 21 21 ) to another chiral point group ( P 21 ). The exceptional dielectric response in the vicinity of 202 K exhibits remarkable dielectric anomalies along the b ‐axis direction than the other two directions. The electric hysteresis loop under 100 K directly indicates it is a potential ferroelectric material.